Burnout levels in neonatal intensive care nurses and its effects on their quality of life - (:unkn) unknown (AUSTRALIAN NURSING FEDERATION, 2013)
Objective The purpose of this study was to investigate burnout levels of nurses working in a neonatal intensive care unit (NICU) and the effects of burnout on their quality of life. Design This was a descriptive and correlational study. The researchers obtained data using a questionnaire to uncover the demographic and occupational characteristics of the nurses, and conducted face-to-face interviews via the Maslach Burnout Inventory (MBI) and the World Health Organization Quality of Life-BREF (WHOQOL-BREF). Setting The NICU of two state hospitals located in the north of Turkey. Subjects A total of 80 nurses. Main outcome measures Levels of burnout experienced. Results The score means of emotional exhaustion, depersonalisation and personal accomplishment were 14.90 +/- 5.53, 3.87 +/- 2.77 and 11.43 +/- 4.63, respectively. The results showed the nurses had burnout at moderate levels with regard to emotional exhaustion and personal accomplishment, and low levels of depersonalisation. In addition, the study showed a significant negative relationship in many sub-scales of the burnout and quality of life scale. Conclusion The nurses experienced moderate burnout in emotional exhaustion and personal accomplishment. The study found that, as burnout level increased, the quality of life of the nurses decreased. It is suggested that several measures must be taken to prevent burnout in nurses.
Keywords: neonatal intensive care unit; nursing; burnout; quality of life; JOB-SATISFACTION; STRESS